Morphological Effects of Heat Stress on Cattle Kidney - Akosman, Murat Sırrı; Türkmenoğlu, İsmail; Demirkan, Aysun Çevik; Özdemir, Vural; Akalan, Mehmet Aydın (Journal of Morphological Sciences, 2018)
Introduction Cattle kidney is an interesting organ because of its individual morphological structure and the mobility of the left kidney. The effects of heat stress on animal yield have been previously researched. However, no data could be obtained during the literature research about the effects of heat stress on the morphological structure of cattle kidneys.Materials and Methods In the present study, morphometric measurements were performed on the left and right kidneys of male and female Holstein cattle. The kidney samples were collected in the summer and winter seasons to assess the effects of heat stress. A scale, water overflow, and a Mitutoyo CDN-P20PMX caliper (Mitutoyo Corporation, Kanagawa, Japan) were used to obtain the morphological structural data of the total kidney, and stereological sampling methods with microscopy were performed to investigate the glomerulus density per unit area and the diameter of the glomerulus.Results Morphological changes on the kidneys were observed after the measurements.Conclusion It can be said that heat stress may cause morphologic changes on cattle kidneys.
Keywords: cattle; heat stress; kidney; morphometry; stereology